Reflexive rules as content: the case of deictic demonstratives - Calado Barbosa, Eduarda (2019)
Determining what content is expressed by a demonstrative when its reference cannot be determined is a problem for those who assume that demonstrative reference is cognized by interpreters and demonstrative meaning has a mere indicative role. Here, I explore a concept of content that gives meaning a cognitively relevant role, namely, John Perry’s classificatory concept of content. With that purpose, I compare the interpretation of a deictic demonstrative in two cases: for an eavesdropper and a conversational participant, aiming to show that meaning, in the form of reflexive rules, can be recruited to play the role of content when information (in the speech situation) is scarce.